Suitability of Islamic Consumption Theory with the Concept of Decluttering as a Preventing Factor for Impulsive Buying Behavior - Noviyanti, Ririn (Universitas Al-Qolam Malang, 2024)
This research aims to determine the suitability of Islamic consumption theory with the concept of decluttering as a factor preventing impulsive buying behavior in society. By using qualitative descriptive methods, researchers try to observe phenomena that occur in the field regarding impulsive buying and the implementation of decluttering activities that are currently being widely followed and then relate their suitability to the principles of consumption in Islam. The results of this research show that there is a compatibility between the theory of consumption in Islam and the concept of decluttering as a prevention of impulsive buying behavior in four indicators, namely indicators of meeting needs, usefulness, goals and financial management. Judging from the indicators of fulfillment of needs, both of them prioritize consideration of fulfilling needs first compared to fulfilling desires alone. From indicators of usefulness in consumption, Islam prioritizes blessings. In the concept of decluttering, the benefits that arise are a calm and peaceful life by not accumulating a lot of items and prioritizing using existing items according to needs. From the goal indicator, both have a goal of happiness. Islam, apart from seeking world happiness, must also pay attention to the happiness of the afterlife. From both financial management indicators, both of them are very concerned about financial income and expenses. So. finances are more disciplined and focused, but on the other hand, minimizing wastefulness and stinginess.